PEMANFAATAN DAUN SIRIH (Piper betle Linn) SEBAGAI BAHAN PEMBUATAN HANDS SANITIZER ALAMI DALAM USAHA MENGATASI DAMPAK COVID-19 BAGI MASYARAKAT KELURAHAN TANJUNG PINANG, PALANGKA RAYA - Misrita Misrita; Wahyudi Wahyudi; Nidia Najati; Imam Qalyubi (Agrienvi: Jurnal Ilmu Pertanian, 2020)
Cases of the coronavirus pandemic in Indonesia are increasing and spreading throughout Indonesia, including the Tanjung Pinang urban village, Palangka Raya. This area is one of the areas that have quite high confirmed casualties, so one of the ways used to overcome the impact of the widespread of the Coronavirus is to clean hands regularly using hand sanitizer containing alcohol or washing hands with soap. and running water. Some hand sanitizer preparations can be found on the market by using it quite simply and quickly, namely by dropping it on the palm of the hand, then flattening it on the surface of the hand. However, it usually contains a lot of alcohol and antiseptics in the form of synthetic chemicals which are relatively expensive and often cause skin health problems, for example, dry skin (decrease in normal skin moisture). Therefore, it is necessary to look for an antiseptic from natural ingredients that are relatively cheaper, safe, effective, and easy to obtain, one of the examples is betel and orange leaves. Natural hand sanitizers themselves have many advantages, including being an alternative for people who have allergies or are sensitive to chemicals; the material is very easy to get; little/cheap capital; and it doesn't take a lot of time in the manufacturing process. Selection of betel leaf as the main ingredient in natural hand sanitizers because betel leaves contain antiseptic properties that can kill germs. The addition of lime juice has a function as a natural preservative that is high in antioxidants. Providing education to community groups in Tanjung Pinang village, Pahandut district, aims to help housewives in utilizing one of the family medicinal plants (TOGA) as well as helping to provide easy and inexpensive solutions to get hand sanitizers which are currently the target of all people due to the Covid-pandemic. 19. The making of this article uses secondary data that comes from linked references and experimental data. Keywords: hands sanitizer, natural, betel leaf.